Molecular Cloning of Hypervariable Regions (HVRII) from Cellulose Synthase (CesA) Gene in Neolamarckia cadamba - Wei-Seng, Ho; Shek-Ling, Pang; Wee-Yang, C; M., Sim (International Academy Publishing (IAP), 2014)
Neolamarckia cadamba or locally known as Kelampayan, is one of the fast growing plantation tree species that holds great prospect as a renewable bioresources for plywood, pulp and paper, and biofuel industries. Sufficient information on cellulose synthase (CesA) gene, especially the hypervariable region II (HVRII) component involved in wood formation of Kelampayan is imperative for future applications. This region is thought to play a role in interaction with other unique cell-type-specific proteins involved in the biosynthesis of cellulose. The aim of this study was to identify and clone the HVRII regions of cellulose synthase gene from the developing xylem tissues of Kelampayan. The cDNA of cellulose synthase HVRII regions was amplified using reverse transcription-PCR (RT-PCR) approach using degenerate primers. Three clones, namely NcCesA1HVRII (520bp), NcCesA2HVRII (580bp) and NcCesA3HVRII (620bp) were successfully sequenced and characterized. NcCesA1HVRII and NcCesA3HVRII were clustered into two distinct clades implicated with secondary cell wall development whereas NcCesA2HVRII has renamed to NcCslD1HVRII due its high similarity with various plants’ CslD-HVRII. This study provides an easier and faster access to NcCesAHVRII sequences to further understand the role of NcCesA/NcCslD protein for future applications such as selecting trees with optimal cellulose content required for specific industries.